TIPE SITOLOGI DUA SPESIES PTERIS DALAM HUBUNGANNYA DENGAN KETINGGIAN TEMPA - Siti Zubaidah (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2001)
A cytological study of the two species of Pteris (Pteris biaurita and Pteris tripartita) growing around Malang was carried out. A hypothesis stated that ploidy was enchanched by cold weather. Those study want to find out the correlation between the altitude (with different temperatures) and ploidy of the two species. Cytological type and ploidy examined by chromosome number counting, using standart squash method. The result of this research showed that Pteris biaurita and Pteris tripartite have two cytotypes, 2n= 58 (2x or diploid) and 2n= 116 (4x or tetraploid). There was no correlation between the ploidy level of Pteris biaurita and the altitude, but the ploidy level of Pteris tripartite apt to be raise in higher altitude.